An Important Landmarks Construction for a GIS-Map based on Indexing of Dolly Images - Abdulkadhem Abdulkareem Abdulkadhem; Tawfiq A. Al-Assadi (Institute of Advanced Engineering and Science, 2019)
In this paper, we describe the construction of important landmarks of roads in the GIS environment. The system uses the corners between more than two roads as an important landmarks. In this corner points will be saving a number of images, each one represents the movement direction between two segment roads. The objective of our work is to build the geo-database repository depend on the GIS (vector data) and multimedia (raster data) information. This paper considered as a preprocessing step for a roadmap discovery of video film when the input to the system is a dolly video film of roads with absence the GPS locations of frames video, and the output is the pathway (route) on the map inside the GIS environment. This work considered as a starting point for multimedia query inside the GIS environment. That’s mean when query the GIS system about a particular image or video, the GIS system must be able to know and determine the location of this image or video file on the map. Thus, the first step for doing this process needs to building and constructing an appropriate database for matching process later.